Application of Bacillus spp. and Potassium Fertilizer Against Corn Downy Mildew Disease - Ratna Dwi Hirma Windriyati; Rifqi Adisonda (G-Tech: Jurnal Teknologi Terapan, 2026)
Downy mildew is an important disease in corn cultivation caused by Peronosclerospora spp. There are many different pathogen species such as P. maydis, P. sorghi. Losses reach 50-80% in corn fields. The use of synthetic fungicides has a negative impact because it destroys natural enemies, resulting in pathogen resistance and plant residues. Balanced biological agents and fertilization are solutions to replace chemical fungicides. The aim of this study was to obtain the best dosage of Bacillus sp. and potassium fertilizer to suppress downy mildew and corn growth. The research method used a factorial Randomized Block Design (RBD). The dosage of Bacillus sp. was B0 (0 g), B1 (15 ml), B2 (20 ml). The dosage of potassium fertilizer (KCl) was 3 K0 (0 g/plant), K1 (6 g/plant), K2 (9 g/plant). There were 9 treatment combinations, 3 replications, so there were 27 treatment units. Plant height, number of leaves, temperature, humidity, disease incidence and disease intensity were observed. The treatment of the biological agent Bacillus spp. and the best potassium fertilizers are B1K0, B2K0 and B2K2 which are able to suppress the incidence of corn downy mildew disease, but are not yet able to produce plant height and number of corn leaves.